DETERMINATION OF THE ROTATION PARAMETERS OF REFERENCE ARTIFICIAL SATELLITE AJISAI AND SYNCHRONIZATION OF THE PHOTOMETRIC CHANNELS - Koshkin, N. I.; Korobeinikova, E. A.; Strakhova, S. L.; Shakun, L. S.; Lopachenko, V. V. (Одеські астрономічні публікації, 2009)
The aim of the present study is to obtain the adjusted current coordinates of the rotation pole of artificial satellite Ajisai and the up-to-date sidereal period of its rotation. To do that, the light curves obtained in Odessa during 2009-2010 are considered. Using both the Ajisai pole’s coordinates and the reduced null point of the hardware-based time scale, has made it possible to improve the timing of the observed flashes of its brightness. By the accurate timing of the simultaneous photometric observations of Ajisai satellite the photometric channels synchronization at the stations in Odessa and Eupatoria is accomplished. The further photometric observations of that satellite are necessary to construct a theory of its rotation about the centre of mass; that will allow of its using as a reference source of the time-calibrated optical signals for any ground-based observatories.